Propranolol for infantile hemangiomas: a preliminary report on efficacy and safety in very low birth weight infants - Erbay, Ayşe; Sarialioglu, Faik; Malbora, Bariş; Yildirim, Selman Vefa; Varan, Birgül; Tarcan, Aylin; Gülcan, Hande; Demir, Senay; Derbent, Murat; Uslu, Nihal; Abbasoğlu, Aslihan (The Turkish Journal of Pediatrics, 2010)
Despite the relatively recent introduction of propranolol in the treatment of infantile hemangiomas, there can be little doubt of its efficacy. With regard to safety issues, there are no prior data for very low weight infants. In this study, we used propranolol in preterm and very low weight infants. We used clinical criteria to assess the response to the therapy. We noted all side effects expected from beta-adrenergic blocking drugs, and followed the patients' weight gain during propranolol treatment. Objective, clinical evidence of hemangioma regression was seen after two months in all patients. None of the patients required treatment discontinuation due to adverse side effects. During the propranolol treatment, weight gain was normal in all patients. To the best of our knowledge, this is the first report on the use of propranolol in preterm and very low weight infants, and also the first report from Turkey on the use of propranolol in infantile hemangiomas.